Characterization of the Oral Microbiome Among Children With Type 1 Diabetes Compared With Healthy Children - Moskovitz, Moti; Nassar, Mira; Moriel, Nadav; Cher, Avital; Faibis, Sarit; Ram, Diana; Zangen, David; Yassour, Moran; Steinberg, Doron (Frontiers in Microbiology, 2021)
Aim: Current microbiome profiling of type 1 diabetes mellitus (T1D) patients is mostly limited to gut microbiome. We characterized the oral microbiome associated with T1D in children after the onset of the disease and explored its relationship with oral physiological factors and dental status. Methods: This cohort study comprised of thirty-seven children aged 5 to 15 years with T1D and twenty-nine healthy children matched in age and gender. Unstimulated whole saliva was collected from diabetic and non-diabetic children, in the morning after brushing their teeth and a fasting period of at least one hour before sampling. 16S rRNA gene-based analysis was performed by Powersoil Pro kit by Qiagen and Phusion High-Fidelity PCR Master Mix. Oral physiological and dental parameters studied included decayed, missing, and filled teeth (DMFT) index, salivary flow rate, and salivary pH, glucose, calcium, phosphate, and urea levels. Results: Of the identified 105 different genera and 211 different species, the most abundant genera were Streptococcus, Prevotella, Veillonella, Haemophilus and Neisseria. Streptococcus was more abundant in T1D children. The diabetes group had 22 taxa at the genus level and 33 taxa at the species level that were not present in the control group and the control group exhibited six taxa at the genus level and nine taxa at the species level that did not exist in the diabetes group. Additionally, Catonella, Fusobacterium, and Mogibacterium differed between healthy and T1D subjects. Eight species and eight subspecies were significantly more abundant among healthy children than in T1D children. Porphyromonas and Mogibacterium genera were significantly correlated with salivary parameters. We found similarities between taxa revealed in the present study and those found in gut microbiome found in type 1 diabetes mellitus according to gutMDisorder database. Conclusions: Salivary microbiome analysis revealed unique microbial taxa that differed between T1D children and healthy subjects. Several genera found in the saliva of T1D children were associated with gut microbiome in T1D individuals.